2018
DOI: 10.1155/2018/9194362
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Radix Astragali Water Abstract on Energy Metabolism in Rat Yang‐Deficiency Cold Syndrome Model through PPAR Signaling Pathway

Abstract: Radix Astragali (RA) herb with warm property and significant “tonifying qi” effects is indicated for the syndrome of internal cold due to Yang deficiency. The purpose of this research was to explore effects of Radix Astragali (RA) through PPAR signaling pathway on gene expression profiles related to energy metabolism in rats with the Yang-deficiency cold (YDC) syndrome, for identifying the pathological mechanism of Yang-deficiency cold (YDC) syndrome and the effects mechanism of RA. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, many studies have reported that microalgae have high antiradical activity coming from their unique chemical structure (2). Furthermore, scientists are trying to find instant and non-invasive techniques to explore the scientific principles of microalgae phytochemicals' functional principles, especially bioactive macromolecules and micromolcules (3). These phytochemicals increase the media antioxidant, anticancer, and other physicochemical potentials (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have reported that microalgae have high antiradical activity coming from their unique chemical structure (2). Furthermore, scientists are trying to find instant and non-invasive techniques to explore the scientific principles of microalgae phytochemicals' functional principles, especially bioactive macromolecules and micromolcules (3). These phytochemicals increase the media antioxidant, anticancer, and other physicochemical potentials (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao. As a highly potent herb widely used to treat various diseases, AR has played an indispensable role in healthcare throughout Chinese history [1,2]. Traditionally, AR is used for the treatment of anemia, weakness, fever, wounds, chronic fatigue, multiple allergies, loss of appetite, uterine bleeding and uterine prolapse [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To better understanding the material basis of TCM syndrome, many studies have disclosed the correlation of syndrome differentiation with objective indicators, including endocrine hormone (adrenocorticosteroids, thyroid hormones, prostaglandins), plasma cyclic nucleotides (cAMP, cGMP, and their dynamic balance), as well as energy metabolism situation, 14,15 which have been applied as the evaluation index for TCM treatment. 16,17 However, TCM syndrome is complex, and the syndrome evolution is not always clear. During the HSCT, we found that the changing of TCM syndrome occurred much more rapidly, and the deviation of "Yin" and "Yang" were more obvious, thus suggesting that HSCT can also be an ideal disease model for observing TCM syndrome evolution and verifying the material basis of "Yin", "Yang", as well as "blood stasis" syndrome in our AA patients.…”
mentioning
confidence: 99%